Socio-Cognitive Aspects of Interoperability: Understanding Communication Task Environments among Different Organizations - Kwon, Gyu Hyun; Smith-Jackson, Tonya L.; Bostian, Charles W. (ASSOC COMPUTING MACHINERY, 2011)
Emergency communication systems (ECS) are a key element in collaborations among different public safety organizations. The need for interoperability in emergency communication systems has hastened the development of interoperable communication technology that is an enabling technology to automatically identify environmental variables including appropriate radio frequencies and to connect different networks used by different organizations. Even though the technology has been researched from many perspectives and has shown that is possible to connect different organizations, there still remain many issues in terms of socio-cognitive aspects. Thus, this study examines the socio-cognitive dimensions of interoperability, which equal the technical dimensions of the problem in importance. The existential-phenomenological study reported here used semistructured interviews to reconceptualize interoperability in the public safety communication domain. Based on 11 interviews with public safety workers, five important factors were identified that have a major impact on the effectiveness of interoperable groups: information sharedness, operational awareness, communication readiness, adaptiveness, and coupledness. Based on these main concepts, high-level suggestions are provided to guide the design of a new public safety communication system. The results can be directly applied to identify the requirements of communication systems and can be extended to design collaboration systems under stressful environments.
Keywords: LOOSELY COUPLED SYSTEMS; SENSEMAKING; SENSE